The modified activity of prolyl 4 hydroxylases reveals the effect of arabinogalactan proteins on changes in the cell wall during the tomato ripening process - Kutyrieva-Nowak, Nataliia; Leszczuk, Agata; Ezzat, Lamia; Kaloudas, Dimitris; Zając, Adrian; Szymańska-Chargot, Monika; Skrzypek, Tomasz; Krokida, Afroditi; Mekkaoui, Khansa; Lampropoulou, Evangelia; Kalaitzis, Panagiotis; Zdunek, Artur (Frontiers in Plant Science, 2024)
Arabinogalactan proteins (AGPs) are proteoglycans with an unusual molecular structure characterised by the presence of a protein part and carbohydrate chains. Their specific properties at different stages of the fruit ripening programme make AGPs unique markers of this process. An important function of AGPs is to co-form an amorphous extracellular matrix in the cell wall-plasma membrane continuum; thus, changes in the structure of these molecules can determine the presence and distribution of other components. The aim of the current work was to characterise the molecular structure and localisation of AGPs during the fruit ripening process in transgenic lines with silencing and overexpression of SlP4H3 genes (prolyl 4 hydroxylase 3). The objective was accomplished through comprehensive and comparative in situ and ex situ analyses of AGPs from the fruit of transgenic lines and wild-type plants at specific stages of ripening. The experiment showed that changes in prolyl 4 hydroxylases (P4H3) activity affected the content of AGPs and the progress in their modifications in the ongoing ripening process. The analysis of the transgenic lines confirmed the presence of AGPs with high molecular weights (120-60 kDa) at all the examined stages, but a changed pattern of the molecular features of AGPs was found in the last ripening stages, compared to WT. In addition to the AGP molecular changes, morphological modifications of fruit tissue and alterations in the spatio-temporal pattern of AGP distribution at the subcellular level were 2 detected in the transgenic lines with the progression of the ripening process. The work highlights the impact of AGPs and their alterations on the fruit cell wall and changes in AGPs associated with the progression of the ripening process.